Strategies registered nurses use to implement integrated primary health care in Maseru District, Lesotho - Posholi, Mamonaheng (University of the Free State, 2019)
Integrated primary health care (IPHC) is a fundamental method of service delivery at a primary level of care. Registered nurses in charge and registered nurses at health centres are the main implementers of IPHC, and their main focus is to deliver a package of combined services based on each person’s needs. In Lesotho, there are no documented strategies on how registered nurses implement IPHC in Maseru district, Lesotho. The study sought to explore and describe the strategies used by registered nurses who are engaged in the day-to-day implementation of IPHC. A qualitative, exploratory design was applied and the nominal group technique used to collect data. The researcher randomly selected eight health centres where IPHC was implemented and recruited the registered nurses who had been providing IPHC for at least one year at the selected health centres. Two nominal groups were held, one with registered nurses in charge of the health centres, and another with registered nurses working at the health centres. Each group had a separate session, which was conducted by an expert facilitator who is conversant with the use of the nominal group technique. The findings of the study are provided in the form of prioritised statements made by the participants; the statements were later arranged into themes by the researcher and checked by an expert group of nurse researchers. Four priority themes were identified. Participants indicated that they used the following four main strategies to implement IPHC, namely, organisation of services around the health centre, person-centred care, collaboration and staff capacity. The participants indicated that they organised services around the health centre by four means: service delivery through referrals to different departments within the health centre (supermarket approach), utilising available human resources, timing (providing all services needed during one visit) and documentation (proper documentation of care in registers and booklets). The registered nurses ensure that care is person-centred through giving health the relevant information. Collaboration with community structures (community health workers and health centre committees) is also practiced to implement IPHC. Lastly, staff capacity is built through attendance of frequent workshops and sharing of information among all the staff at the health centre.
Dissertation (M.Soc.Sc. (Nursing))--University of the Free State, 2019
Keywords: Integrated primary health care (IPHC); Registered nurses; Maseru District, Lesotho; Strategies; Implementation